Irisin Attenuates Hepatic Stellate Cell Activation and Liver Fibrosis in Bile Duct Ligation Mice Model and Improves Mitochondrial Dysfunction - Thuy Linh Lai; So Young Park; Giang Nguyen; Phuc Thi Minh Pham; Seon Mee Kang; Jeana Hong; Jae-Ho Lee; Seung-Soon Im; Dae-Hee Choi; Eun-Hee Cho (Endocrinology and Metabolism)
Background Liver fibrosis is a common outcome of chronic liver disease and is primarily driven by hepatic stellate cell (HSC) activation. Irisin, a myokine released during physical exercise, is beneficial for metabolic disorders and mitochondrial dysfunction. This study aimed to explore the effects of irisin on liver fibrosis in HSCs, a bile duct ligation (BDL) mouse model, and the associated mitochondrial dysfunction. Methods In vitro experiments utilized LX-2 cells, a human HSC line, stimulated with transforming growth factor-β1 (TGF-β1), a major regulator of HSC fibrosis, with or without irisin. Mitochondrial function was assessed using mitochondrial fission markers, transmission electron microscopy, mitochondrial membrane potential, and adenosine triphosphate (ATP) production. In vivo, liver fibrosis was induced in mice via BDL, followed by daily intraperitoneal injections of irisin (100 μg/kg/day) for 10 days. Results In vitro, irisin mitigated HSC activation and reduced reactive oxygen species associated with the TGF-β1/Smad signaling pathway. Irisin restored TGF-β1-induced increases in fission markers (Fis1, p-DRP1) and reversed the decreased expression of TFAM and SIRT3. Additionally, irisin restored mitochondrial membrane potential and ATP production lowered by TGF-β1 treatment. In vivo, irisin ameliorated the elevated liver-to-body weight ratio induced by BDL and alleviated liver fibrosis, as evidenced by Masson’s trichrome staining. Irisin also improved mitochondrial dysfunction induced by BDL surgery. Conclusion Irisin effectively attenuated HSC activation, ameliorated liver fibrosis in BDL mice, and improved associated mitochondrial dysfunction. These findings highlight the therapeutic potential of irisin for the treatment of liver fibrosis.